Characteristics, Genesis And Classification of Reddish Soils from Sidamo Region of Ethiopia - Atengo, Abayneh Esayas (2005)
Sesquioxidic reddish soils are one of the major agricultural soils in Ethiopia. They are intensively cultivated for coffee. Accurate and detailed information on the nature and properties of these soils is necessary to improve and sustain their agricultural productivity. To achieve this objective, ten representative pedons developed from different parent materials of volcanic and metamorphic origin in Sidamo highlands, Ethiopia, were investigated. Feldspar and ferromagnesians are the dominant minerals in the basalt, whereas quartz, feldspar and minor amounts of hornblende phenocrysts embedded in a groundmass of volcanic ash and glass are dominant in the ignimbrites and rhyolite. Zeolites (clinoptilolite and mordenite) were discovered in substantial amounts in the ignimbrites. The soil texture, profile depth and morphology of the soils vary according to parent material groups. The soil pH values range from 4.2 to 6.8 and due to leaching of bases; soils developed under udic moisture regime have the lowest pH. The pHNaF values are generally less than 9.4, indicating that the soils are not allophanic. The cation exchange capacity (CEC) varies according to parent material groups in the order of ignimbrite > rhyolite > basalt > gneiss with the value of 4.0 to 39.6 cmolc/kg soil. Exchangeable cations and available micronutrients content of the surface soils are higher than the subsurface soils. This is attributed to the cycling of nutrients by the plants. Available phosphorus (P) is low (< 6 mg P/kg soil) and it is the most limiting nutrient for crop production in the area, although copper and potassium are marginal. The P sorption studies indicated that the soils are high P sorbing soils, with the subsurface soils have higher P sorption capacity than the surface soils. The P sorption characteristics of the soils have significant positive correlation with clay content and different forms of Fe and Al, and negative correlation with soil pH. The P requirement of the surface soils varies from 41 to 142 mg P kg-1 soil. The sand and silt fractions are dominated by quartz and varied amounts of feldspar. The clay fractions are dominated by kaolinite and minor amounts of illite. The relative abundance of illite and feldspar is higher in the soils from younger geological units (ignimbrites). Iron (Fe) is dominantly in crystalline form, whereas aluminium (Al) is in amorphous from in the soils. Hematite, maghemite and goethite are the common Fe-oxide minerals in the clay fractions. The relative abundance of goethite is higher in soils from higher altitudes (cooler and wetter environments). The Al substitution for Fe in hematite and goethite varied from 7 to 24 and from 14 to 39 mole % Al, respectively. The relative proportion and distribution of coarse to fine materials (c/f-ratio) varied according to parent material groups from open porphyric in basaltic soils to single spaced porphyric in gneissic soils. Microlaminated clay coatings are abundant in soils derived from the younger geological units (ignimbrites) compared to basaltic and gneissic soils. The pedogenetic processes in the soils were mainly related to the weathering of primary minerals, clay illuviation, bioturbation and translocation of Fe-oxides to saprolitic layers. Halloysite is mainly restricted in the saprolitic layers, whereas kaolinite is dominant in the soil solum. The Chuko and Morocho pedons, derived from Quaternary ignimbrites and characterized by appreciable clay illuviation in the B horizons are classified as Kandic Paleustalfs (Soil Survey Staff, 1999) or Profondic Lixisols (WRB, 1998), whereas the Dengora pedon derived from similar material is classified as Typic Rhodustult or Hyperdystric Acrisol due to low base saturation. The rest of the soils, due to uniform clay distribution with depth and presence of horizons of very low CEC (oxic horizon) are classified as Oxisols (Eutrustox, Eutrudox, Haplustox, Hapludox and Kandiudox) or Ferralsols (Humic Ferralsol, Rhodic Ferralsol and Hypereutric Ferralsol). The surface charge of the soils is dominated by permanent negative charge with minor amounts of variable charge. There is an increase in AEC and a decrease in CEC with soil depth, indicating higher potential leaching losses of cations. Comparison of the fingerprint (FP) and the compulsive exchange methods indicated that the FP method can satisfactorily predict the basic nutrient retention capacity of the soils